A Selectable and Excisable Marker System for the Rapid Creation of Recombinant Poxviruses - Rintoul, Julia L.; Wang, Jiahu; Gammon, Don B.; van Buuren, Nicholas J.; Garson, Kenneth; Jardine, Karen; Barry, Michele; Evans, David H.; Bell, John C. (PLOS ONE, 2011)
Background Genetic manipulation of poxvirus genomes through attenuation, or insertion of therapeutic genes has led to a number of vector candidates for the treatment of a variety of human diseases. The development of recombinant poxviruses often involves the genomic insertion of a selectable marker for purification and selection purposes. The use of marker genes however inevitably results in a vector that contains unwanted genetic information of no therapeutic value. Methodology/Principal Findings Here we describe an improved strategy that allows for the creation of marker-free recombinant poxviruses of any species. The Selectable and Excisable Marker (SEM) system incorporates a unique fusion marker gene for the efficient selection of poxvirus recombinants and the Cre/loxP system to facilitate the subsequent removal of the marker. We have defined and characterized this new methodological tool by insertion of a foreign gene into vaccinia virus, with the subsequent removal of the selectable marker. We then analyzed the importance of loxP orientation during Cre recombination, and show that the SEM system can be used to introduce site-specific deletions or inversions into the viral genome. Finally, we demonstrate that the SEM strategy is amenable to other poxviruses, as demonstrated here with the creation of an ectromelia virus recombinant lacking the EVM002 gene. Conclusion/Significance The system described here thus provides a faster, simpler and more efficient means to create clinic-ready recombinant poxviruses for therapeutic gene therapy applications.